Effectiveness of interventions on the stress management of schoolteachers: a systematic review and meta-analysis - Paudel Netra Raj; Adhikari Bidhya Acharya; Prakash K.C.; Kyrönlahti Saila; Nygård Clas-Håkan; Neupane Subas (BMJ Publishing Group, 2022)
Background This systematic review aimed to analyse the effectiveness of interventions on the stress management of schoolteachers.
Methods We searched the Medline, PsycINFO, CINAHL and Education Research Complete until 30 November 2021, to identify relevant studies using relevant key words. Job or occupational stress was used as the outcome measure. Stress was defined as Perceived Stress Scale, Teacher Stress Inventory, Maslach Burnout Inventory, Teacher's Distress, Brief Symptoms Inventory or Global Severity Index. Study selection, data extraction, risk of bias assessment was performed by two independent reviewers. The pooled estimate of the effect by the type of outcome measurement tool and by type of interventions used was calculated using random effects meta-analysis. We used Grades of Recommendations, Assessment, Development and Evaluation to assess the overall quality of the evidence.
Results We reviewed 26 studies, of which 24 were randomised trials and 2 pre-test/post-test studies. Based on meta-analysis, a positive effect of intervention (pooled estimate -1.13, 95% CI -1.52 to -0.73) with high heterogeneity among studies (χ2=426.88, p<0.001,I2=94%) was found by type of interventions used. Cognitive-behavioural therapy had the strongest positive effect, followed by meditation among the types of interventions studied. We identified evidence of a moderate quality for interventions aiming to manage the stress level of schoolteachers.
Conclusions The meta-analysis showed a positive effect of interventions, suggesting that interventions might reduce the stress level among teachers. The quality of the evidence was moderate.
PROSPERO registration number CRD42021225098